2002
DOI: 10.1159/000069047
|View full text |Cite
|
Sign up to set email alerts
|

Under What Circumstances Can Seizures Produce Hippocampal Injury: Evidence for Age-Specific Effects

Abstract: Mesial temporal sclerosis (MTS) is the characteristic hippocampal pathology of temporal lobe epilepsy in adults. Both clinical and experimental studies indicate that although the immature brain is highly susceptible to seizures, it is more resistant to the development of the seizure-induced hippocampal pathology akin to MTS, compared with the adult brain. However, seizures in the immature brain may produce age-specific effects on hippocampal morphology or function. The spectrum of these effects is still unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 103 publications
0
16
0
3
Order By: Relevance
“…As susceptibility to seizure‐induced cell death can be modulated by the duration and severity of seizure induction (Berger et al 1986; Ferraro et al 1995; Galanopoulou et al 2002; Holmes 2002; Sucholmelova et al 2006), we also characterized congenic strains for seizure activity following kainate administration. Following kainate injection, we found a significant decrease in the latency to first seizure by anova in FVB.B6‐ Sicd2 mice ( n = 42) as compared to FVB‐like littermates ( n = 14; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As susceptibility to seizure‐induced cell death can be modulated by the duration and severity of seizure induction (Berger et al 1986; Ferraro et al 1995; Galanopoulou et al 2002; Holmes 2002; Sucholmelova et al 2006), we also characterized congenic strains for seizure activity following kainate administration. Following kainate injection, we found a significant decrease in the latency to first seizure by anova in FVB.B6‐ Sicd2 mice ( n = 42) as compared to FVB‐like littermates ( n = 14; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our data confirm previous findings that the genetic background of mice significantly affects the susceptibility of hippocampal neurons to damage by pilocarpine (Borges et al, 2003; Müller et al, 2009a; Shibley and Smith, 2002; Winawer et al, 2007), and extends these findings to a comparison of a large number of inbred strains. As prior studies have suggested that differential susceptibility to seizure-induced cell death could result from a reduction in seizure activity (Berger et al, 1986; Ferraro et al, 1995; Galanopoulou et al, 2002; Holmes, 2002; Sucholmelova et al, 2006), we examined several seizure parameters. Irrespective of mouse strain examined, the latency to onset of status epilepticus or severity of seizure activity, as defined by the percentage of mice achieving stage 4/5 severe seizures, was not different.…”
Section: Discussionmentioning
confidence: 99%
“…The early periods of life, when brain development is still incomplete, susceptibility to seizures is increased [3, 4]. However, a combination of biological factors (genetic, age-related processes, epigenetic or environmental factors) protect neurons from seizure-induced injury, epileptogenesis, or mortality to a greater extent than the adult brain is protected [5]. It is increasingly recognized that seizures may leave their imprint on the developing brain by altering the way that neurons differentiate, connect, and communicate to each other, even if, in many cases, such changes may be ultimately compensated for.…”
Section: Introductionmentioning
confidence: 99%